Factors causing cost overruns in public hospital construction in developing countries: a case from Vietnam - Nhat Minh Huynh; Anh Tuan Le; Long Le-Hoai; Huu Tho Nguyen (Journal of Asian Architecture and Building Engineering)
This research addresses the persistent problem of cost overruns in the construction of public hospitals in Vietnam, a challenge amplified by the increased demands and complexities brought on by the COVID-19 pandemic. Cost overruns not only increase financial strain but also miss opportunities to improve healthcare quality and accessibility. This paper delves into the specific issues contributing to these overruns, focusing exclusively on public hospitals which operate under distinct challenges compared to their private counterparts. Through a comprehensive and systematic methodology, the study incorporates both qualitative and quantitative analyses. It involves a broad literature review, expert consultations, a detailed survey, and rigorous statistical evaluations. The findings identify and rank 43 critical factors, revealing significant correlations across different stakeholder perspectives and confirming these factors in real-world hospital construction projects. The study also categorizes these factors into seven distinct groups using Principal Component Analysis (PCA), offering a nuanced understanding of the multifaceted nature of these challenges. Finally, this study suggests several recommendations that could be effective in addressing these issues. This research not only sheds light on the complexities of public hospital construction in Vietnam but also serves as a crucial guide for stakeholders in managing and mitigating cost overruns effectively.